Nation building and international solidarity: Some considerations about Balkans in Italian republican thinking in 19th century - Pasini Piero (Glasnik Etnografskog Instituta SANU, 2015)
In this paper I want to review the thinking of some Italian republicans’ ideologists and patriots for what concerns the matter of National orders of Southern Slavs, with more attention to the Western Balkans. I argue that the Republicans had a particular conception of the National issues, different from the concepts of Nation and Nationality as intended by the Socialists, the Liberals and the Monarchists. Also I would like to underline a particular sensibility on the matter of the Nationality in Balkans by that Italian patriots subjected to the Austrian crown. Of course I will deal with the ideas of Giuseppe Mazzini, that has already been well studied by the Italian, Slav and International historiography, but also the ideas of Tommaseo, Italian from Dalmatia, republican but not on the same positions of Mazzini, of Attilio and Emilio Bandiera, Venetian patriots near to Mazzini’s thinking, but independent in actions and political practice. I will also give some elements about the vision of the International order of liberals, monarchists and, overall, not Austrian’s subjected. The study of those topics appears very current in this period of crisis of the state-nation concept and seems useful to reconsider concepts such as unity, integration and solidarity of Europe and between Nations.